DSP: A tool for probabilistic sex diagnosis using worldwide variability in hip-bone measurements - Pascal Murail; Jaroslav Brůžek; Francis Houët; Eugénia Cunha (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Determination of the sex of human bone remains represents a crucial stage in any palaeoanthropological study. The palaeobiological or palaeoethnological interpretations depend on its reliability. It is acknowledged that the adult hip-bone (os coxae) is by far the best non-population-specific indicator for reliable sex determination of adults. However, we clarify here a certain number of limitations which lower the reliability and ease of application of the usual methods. We propose a new tool—Probabilistic Sex Diagnosis (DSP: Diagnose Sexuelle Probabiliste)—based on a worldwide hip-bone metrical database (2040 adult specimens of known sex from 12 different reference populations). Sex is determined by comparing the specimen’s measurements to those from the database and by computing the individual probability of being female or male, from any combination of at least four variables among ten. This method is very easy to learn and apply; it provides sex diagnosis for any anatomically modern human, whatever population the specimen belongs to. Numerous combinations allow sex diagnosis of either well—preserved hip-bones or damaged ones. DSP is thus useful for both archaeological and forensic purposes. Its accuracy is close to 100%. The DSP computing program is available at the following web link: http://www.pacea.u-bordeaux1.fr/publication/dspv1.html